Awareness and remedy of Coronavirus through The English Languages contributions - Rashid, Md. Harun; Hui, Wang; Shameem, A S M; Hoque, Mahbubul; Islam, Jahirul; Nishi, Shanzida Yesmin; Zamir, Maknoon Binte (International Journal of Psychosocial Rehabilitation, 2020)
Spreading awareness is very important for the world Respiratory Syndrome and viral respiratory disease of serious consequences caused by Coronavirus (CoV19). In this situation, the English language is one of the most important and curtail parts of making awareness in the world population. The world communities have still lack of awareness available protective measures to prevent the transmission of the virus. It is necessary to explore the current information-seeking strategies and preferences through the use of English language, its communication tools among the world population to promote the dissemination of accurate information. This study followed quantitative research, we selected randomly 120 international students for a survey, there had 20 students from China, 20 students from Bangladesh, 20 students from Iraq, 20 students from Pakistan, 20 students from Iran and 20 students from Malaysia. We prepared 30 questioners based on five factors for awareness of coronavirus. The data analysed with the percentage of Agree, Disagree, Strongly Agree, Strongly Disagree and Neutral. The results of this study can play an impotent role for increasing of awareness, campaign and remedy of Corona virus though the English Languages contribution.